1994
DOI: 10.1002/art.1780371120
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of autoantibodies to native 60‐kd ro/ss‐a and denatured 52‐kd ro/ss‐a in eluates from the heart of a child who died with congenital complete heart block

Abstract: Objective. To determine the serologic specificity of acid eluates from tissues of a child who died with congenital complete heart block (CCHB).Methods. Tissues were extracted, acid eluted, and the IgG and antibody titers determined on the eluates by enzyme-linked immunosorbent assay.Results. Antibodies to native 60-kd and denatured 52-kd RoISS-A were found to be enriched only in the heart eluate, and not in the eluates from brain, kidney, and skin.Conclusion. These findings indicate a major role for anti-nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
2

Year Published

1995
1995
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 26 publications
2
36
0
2
Order By: Relevance
“…However, deposition of immune complexes containing anti-double-stranded DNA antibody subsets can induce renal failure (11,12), these antibodies may also deposit directly on the glomerular basement membrane, inducing proteinuria (13). On the other hand, deposition of antibodies to Ro/SSA ribonucleoprotein in fetal cardiac tissues is thought to be associated with congenital heart block (14,15), and autoantibody subsets to ribosomal P proteins have been shown to be able to penetrate into live cells and cause cellular dysfunction (16). Because elevated rates of spontaneous and induced chromosomal damage have been reported in certain autoimmune rheumatic diseases (17,18), deficient DNA repair was observed in chronic ulcerative colitis (19) and SLE (20,21), and defects in poly(ADP-ribose) synthesis have been described in lupus patients and their healthy biological relatives (22,23), we studied the possibility that autoantibodies to F1 and F2 zinc fingers inhibit the PARP catalytic activity and cause the observed pathogenic effects.…”
mentioning
confidence: 99%
“…However, deposition of immune complexes containing anti-double-stranded DNA antibody subsets can induce renal failure (11,12), these antibodies may also deposit directly on the glomerular basement membrane, inducing proteinuria (13). On the other hand, deposition of antibodies to Ro/SSA ribonucleoprotein in fetal cardiac tissues is thought to be associated with congenital heart block (14,15), and autoantibody subsets to ribosomal P proteins have been shown to be able to penetrate into live cells and cause cellular dysfunction (16). Because elevated rates of spontaneous and induced chromosomal damage have been reported in certain autoimmune rheumatic diseases (17,18), deficient DNA repair was observed in chronic ulcerative colitis (19) and SLE (20,21), and defects in poly(ADP-ribose) synthesis have been described in lupus patients and their healthy biological relatives (22,23), we studied the possibility that autoantibodies to F1 and F2 zinc fingers inhibit the PARP catalytic activity and cause the observed pathogenic effects.…”
mentioning
confidence: 99%
“…Although proof of pathogenicity is not definitive, accumulating evidence suggests that anti-SS-A/Ro antibodies contribute to the cardiac and tissue damage in NLE (4,(35)(36)(37). A molecular definition of the SS-A/Ro autoantigens has been provided by the cloning of cDNAs, but little is known about their biologic function other than binding to hY RNAs or their role in disease pathogenesis and tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these antibodies react with their corresponding antigens on the surface of the cells of the conduction system in the heart (Horsfall et al 1991). Although antiRo/SSA antibodies have been eluted from affected fetal cardiac tissue (Reichlin et al 1994), there is no reason to expect the expression of the Ro/SSA protein, a nucleoprotein, in the surface membrane of the cardiac cells. In that regard it is interesting to note that Miranda et al (1998) have shown that apoptotic human fetal cardiomyocytes express Ro and La anti-gens in the surface.…”
Section: The Neonatal Lupus Syndromementioning
confidence: 99%